Surgical Placement of Permanent Pacemaker Following Temporary Trasvenous Pacemaker in a Child with Congenital Heart Block and Moderate Size PDA: A Case Report (Bangladesh Journal of Child Health, 2017)
Abstract not availableBangladesh J Child Health 2016; VOL 40 (2) :124-128